2022
DOI: 10.3390/polym15010145
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in the Processing, Properties, and Applications of Epoxy-Based Natural Fiber Polymer Biocomposites

Abstract: Growing environmental concerns have increased the scientific interest in the utilization of natural fibers for the development of epoxy biocomposite materials. The incorporation of one or more fibers in the production of hybrid epoxy polymer composites has been a subject of discussion. It is interesting to acknowledge that natural/synthetic fiber hybridized epoxy composites have superior properties over natural/natural fiber hybridized epoxy composites. Significant efforts have been devoted to the improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 200 publications
0
5
0
Order By: Relevance
“…On the one hand, the void content of the composites decreases when the fiber content is increased to an optimal value, which contributes to the improvement of the mechanical performance. 18 On the other hand, the addition of plant fiber promotes the heterogeneous nucleation of the matrix, improves the crystallinity, and increases with the increase in fiber content. [70][71][72][73][74] For different composites, the optimal value of fiber content is different, and there exists an upper limit.…”
Section: Content Of Plant Fibersmentioning
confidence: 99%
See 3 more Smart Citations
“…On the one hand, the void content of the composites decreases when the fiber content is increased to an optimal value, which contributes to the improvement of the mechanical performance. 18 On the other hand, the addition of plant fiber promotes the heterogeneous nucleation of the matrix, improves the crystallinity, and increases with the increase in fiber content. [70][71][72][73][74] For different composites, the optimal value of fiber content is different, and there exists an upper limit.…”
Section: Content Of Plant Fibersmentioning
confidence: 99%
“…The content of plant fibers has a significant impact on improving the mechanical properties of composites. On the one hand, the void content of the composites decreases when the fiber content is increased to an optimal value, which contributes to the improvement of the mechanical performance 18 . On the other hand, the addition of plant fiber promotes the heterogeneous nucleation of the matrix, improves the crystallinity, and increases with the increase in fiber content 70–74 .…”
Section: Raw Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It focused on the toughening of diglycidyl ether of bisphenol A (DGEBA) epoxy resin by using solid nanoparticles with other modifiers such as rubbers, thermoplastics, thermosetting resins and diluents. It has been demonstrated that the performance properties of hybrid nanocomposites depend not only on the type and amount of components, and their eventual interactions, but also on the processing conditions [ 197 , 198 , 199 ].…”
Section: Future Trends and Challengesmentioning
confidence: 99%